Inovasi Pelayanan Publik Pada Program Layanan Jelajah Arsip (JELAS) Di Dinas Perpustakaan Dan Kearsipan Kabupaten Sidoarjo - Bernika Sucining Tyas; Susi Hardjati (Public Inspiration : Jurnal Administrasi Publik, 2025)
Innovation in public services has a crucial role and is very necessary as an effort to improve the quality of services to the community. Therefore, the government as executor of its duties is expected to be able to continue to innovate, public service providers need to always innovate, so that people can get services that are more responsive, quality and based on their interests. Including innovation in archives. The Sidoarjo Regency Library and Archives Service is an example of an institution that has succeeded in providing innovative public services in the archives sector by educating young children with a service program called JELAS. JELAS or better known as Jelajah Archives is an innovative activity in the archives field which aims to provide education about personal archives, how to manage them, as well as information related to archival documentation. This type of qualitative descriptive research focuses on the theory of Stephen Robbins (2003: 115), namely that innovation has characteristics/specialties, has characteristics or elements of novelty, through a planned program, has a goal.